Soil Quality Influences Efficacy of Melia azedarach (Sapindales: Meliaceae), Fruit Extracts against Rhipicephalus (Boophilus) microplus (Acari: Ixodidae). (18th October 2014) - De Sousa, Lorena A. D.; Da Costa, Deomar P.; Ferri, Pedro H.; Showler, Allan T.; Borges, LÍgia M. F.
Abstract : Hexane extract of chinaberry, Melia azedarach L., unripe fruits obtained from different municipalities of Goiás State, Brazil, were evaluated on the southern cattle tick, Rhipicephalus ( Boophilus ) microplus (Canestrini), engorged females. Hexanic extracts were assayed in decreasing concentrations from 0.25 to 0.0156% to determine effects on egg production and hatching. Efficacy on engorged females decreased as a result of the extracts from Goiânia (100%), Professor Jamil (97.5 ± 3.0%), Pirenópolis (95.1 ± 2.4%), Morrinhos (86.8 ± 9.4%), Caturaí (41.8 ± 29.3%), and Bela Vista de Goiás (17.1 ± 0.9%) municipalities. Canonical redundancy analysis indicated that the extract bioactivity was positively correlated with soil Ca 2+, Mg 2+, and P and negatively correlated with silt, K +, potential acidity, and organic matter. This study demonstrates that M. azedarach hexanic extract can dramatically reduce R . ( B .) microplus reproductive capacity and that efficacy is strongly influenced by differences in soil constituents between collection sites.